Physical, mechanical, and thermal properties of epoxy composites with woven kenaf and kenaf/cotton fabrics - Ismail, Ahmad Safwan; Jawaid, Mohammad; Sarmin, Siti Noorbaini; Fouad, Hassan; Khiari, Ramzi; Zainudin, E. S. (Springer Science and Business Media B.V., 2025)
Researchers have turned their attention to the potential of lignocellulosic fibre-reinforced composites for various applications. This fibre can take different forms, such as short fibres, long fibres, woven mats, non-woven mats and fabrics. Each form has different properties. This study evaluates the physical, mechanical, dynamic mechanical and thermal properties of woven kenaf (WK) and kenaf/cotton (KC) reinforced bio-epoxy composites. The composites were fabricated using a hand lay-up technique and cured with a hot press. The obtained results show that woven kenaf composites with a 40% fibre loading (WK-FL40: 1.26 g.cm−3) have the highest density, while kenaf/cotton composites (KC-FL35: 8.03%) have the highest void content. Additionally, kenaf/cotton composites exhibit higher water absorption than woven kenaf composites. Under saturated conditions, the highest water absorption is shown by KC-FL40, which is 13.8%. Kenaf/cotton composites have superior mechanical properties correlated to woven kenaf composites, where the best overall mechanical properties are shown by composites KC-FL40 (Tensile strength: 117.95 MPa, Tensile Modulus: 11.23 GPa, Flexural Strength: 154.25 MPa, Flexural Modulus: 9.72 MPa, Impact Strength: 10.42 J/m2). The dynamic mechanical analysis reveals that the storage modulus and peak loss modulus increase with fibre loading, while the tan delta peak decreases with addition of reinforcement. In terms of thermal stability, the incorporation of woven kenaf and kenaf cotton fabric slightly improves thermal stability, with the highest residue at 700 °C shown by composites KC-FL30, which is 20.35. Overall, it can be concluded that kenaf/cotton composites have better overall properties compared to woven kenaf composites. They can be used for various indoor applications, such as food trays for aeroplanes.